Capillary isoelectric focusing of probiotic bacteria from cow's milk in tapered fused silica capillary with off-line matrix-assisted laser desorption/ionization time-of-flight mass spectrometry identification - Horká, Marie; Karásek, Pavel; Salplachta, Jiří; Růžička, Filip; Vykydalová, Marie; Kubesová, Anna; Dráb, Vladimír; Roth, Michal; Slais, Karel (Analytica chimica acta, 2013)
In this study, combination of capillary isoelectric focusing (CIEF) in tapered fused silica (FS) capillary with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) is presented as an efficient approach for unambiguous identification of probiotic bacteria in real sample. For this purpose, bacteria within genus Lactobacillus were selected as model bioanalytes and cow's milk was selected as a biological sample. CIEF analysis of both the cultivated bacteria and the bacteria in the milk was optimized and isoelectric points characterizing the examined bacteria were subsequently determined independently of the bacterial sample origin. The use of tapered FS capillary significantly enhanced the separation capacity and efficiency of the CIEF analyses performed. In addition, the cell number injected into the tapered FS capillary was quantified and an excellent linearity of the calibration curves was achieved which enabled quantitative analysis of the bacteria by CIEF with UV detection. The minimum detectable number of bacterial cells was 2×10(6) mL(-1). Finally, cow's milk spiked with the selected bacterium was analyzed by CIEF in tapered FS capillary, the focused and detected bacterial cells were collected from the capillary, deposited onto the cultivation medium, and identified using MALDI-TOF MS afterward. Our results have revealed that the proposed procedure can be advantageously used for unambiguous identification of probiotic bacteria in a real sample.
Keywords: Cattle; Animals; isoelektrická fokusace; skot; Probiotics; Tapered fused silica capillary; Pasteurization; Lactobacillus; Electrophoresis, Capillary; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Hydrogen-Ion Concentration; Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry; elektroforéza kapilární; Food Analysis; Calibration; Lactic acid bacteria; Milk; pasterizace; kalibrace; analýza potravin; probiotika; Capillary isoelectric focusing; Isoelectric Focusing; spektrometrie hmotnostní - ionizace laserem za účasti matrice; zvířata; mléko; koncentrace vodíkových iontů